Motivations to set up and manage low-fee private schools in India - Mond, Hannah; Prakash, Poorvaja (Education Policy Analysis Archives, 2019)
Low-fee private schools (LFPS) educate some of India’s poorest children. They have grown dramatically over the last decade in India and have changed the country’s educational landscape (Srivastava, 2016), yet there is little conclusive evidence that the schools significantly help their students. Our study aims to better understand why and how the schools have grown, and we use a social entrepreneurship theory – the push and pull theory – to guide our research questions. We interviewed eight owners and asked: “what are the motivations of individual actors in setting up low fee private schools?” and “how do these actors justify continuing their work when presented with empirical research on these schools’ mixed impact on the quality of education they provide? There were more pull than push factors. Owners’ distrust of government schools, and the characteristically low-income nature of the communities drove them to choose the low-fee private school model. They justified their work despite evidence of these schools’ mixed impact, arguing that their schools were different from the regular LFPS and that there is high parental support for their schools. We recommend policies to better support such individuals and provide them with an awareness of alternative paths to contribute to improving education.